2018
DOI: 10.1111/all.13392
|View full text |Cite
|
Sign up to set email alerts
|

Lolium perenne peptide immunotherapy is well tolerated and elicits a protective B‐cell response in seasonal allergic rhinitis patients

Abstract: BackgroundSystemic allergic reactions are a risk for allergen immunotherapy that utilizes intact allergen preparations. We evaluated the safety, efficacy and immune mechanisms of short‐course treatment with adjuvant‐free Lolium perenne peptides (LPP) following a 6‐week dose‐escalation protocol.MethodsIn a prospective, dose‐escalation study, 61 grass pollen–allergic patients received 2 subcutaneous injections of LPP once weekly for 6 weeks. Safety was assessed evaluating local reactions, systemic reactions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…Recent studies confirmed AIT with grass allergen peptides (170 μg over 3 weeks) and depigmented polymerized allergen extracts as safe and effective treatments for local AR caused by grass pollen sensitization. A maximum cumulative dose of 490 μg of the grass pollen peptides was well tolerated with only a few minor adverse reactions . After completing AIT, symptoms can reoccur within a few years but can be prevented by receiving a short course booster.…”
Section: Allergen Immunotherapy (Ait)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies confirmed AIT with grass allergen peptides (170 μg over 3 weeks) and depigmented polymerized allergen extracts as safe and effective treatments for local AR caused by grass pollen sensitization. A maximum cumulative dose of 490 μg of the grass pollen peptides was well tolerated with only a few minor adverse reactions . After completing AIT, symptoms can reoccur within a few years but can be prevented by receiving a short course booster.…”
Section: Allergen Immunotherapy (Ait)mentioning
confidence: 99%
“…A maximum cumulative dose of 490 μg of the grass pollen peptides was well tolerated with only a few minor adverse reactions. 113 After completing AIT, symptoms can reoccur within a few years but can be prevented by receiving a short course booster. This has been demonstrated with recurrent pollen-induced seasonal AR patients that experienced a reduction of symptoms when administered with an ultra-short-course booster AIT using tyrosine-absorbed allergoids containing the adjuvant monophosphoryl lipid A (MPL((R)).…”
Section: Allerg En Immunother Apy ( Ait )mentioning
confidence: 99%
“…Modified allergens such as recombinant allergens, allergoids, and allergen peptides have also recently been developed for use in AIT. Mösges et al have demonstrated that a novel SCIT formulation containing Lolium perenne (perennial ryegrass) peptides can be administrated at higher doses for the relatively short duration of 3 weeks to improve tolerance and significantly increase the levels of specific IgG4 antibodies. These authors further demonstrated that L perenne peptide immunotherapy is not only well‐tolerated, but also able to elicit protective B‐cell responses in seasonal AR patients .…”
Section: Treatmentmentioning
confidence: 99%
“…Mösges et al have demonstrated that a novel SCIT formulation containing Lolium perenne (perennial ryegrass) peptides can be administrated at higher doses for the relatively short duration of 3 weeks to improve tolerance and significantly increase the levels of specific IgG4 antibodies. These authors further demonstrated that L perenne peptide immunotherapy is not only well‐tolerated, but also able to elicit protective B‐cell responses in seasonal AR patients . Indeed, other studies have indicated that recombinant B‐cell epitopes and continuous overlapping peptides are also well‐tolerated in AIT.…”
Section: Treatmentmentioning
confidence: 99%
“…18,19 In addition, immunotherapy with allergen-derived T-cell epitope-based peptides is being trialled in intradermal and subcutaneous formulations. 20,21 These peptides do not invoke IgE responses and mitigate the risk of anaphylaxis, but target the specific, disease-driving T cells. Similarly, the use of hypoallergenic but T-cellreactive allergen peptides derived by proteolytic hydrolysis for grass pollen allergy treatment also shows promise.…”
Section: Allergen Immunotherapy: a Prototype Of Precision Medicinementioning
confidence: 99%